Progress of Spark Plasma Sintering (SPS) Method, Systems, Ceramics Applications and Industrialization - Masao Tokita (Ceramics, 2021)
The spark plasma sintering (SPS) method is of great interest to the powder and powder metallurgy industry and material researchers of academia for both product manufacturing and advanced material research and development. Today in Japan, a number of SPS products for different industries have already been realized. Today’s fifth-generation SPS systems are capable of producing parts of increasing size, offering improved functionality, reproducibility, productivity, and cost. For instance, pure nano-Tungsten Carbide WC powder (no additives) is fully densified with a nano-grain-sized structure for glass lens application in the optics industry. The SPS is now moving from scientific academia and/or R&D proto-type materials level usage to practical industry use product stage utilizing in the field of electronics, automotive, mold and die, cutting tools, fine ceramics, clean energy, biomaterials industries, and others. This paper reviews and introduces the peculiar phenomenon of SPS and the progress of SPS technology, method, development of SPS systems, and its industrial product applications.